WISDOM project XX. – Strong shear tearing molecular clouds apart in NGC 524 - Lu, A; Haggard, D; Bureau, M; Gensior, J; Jeffreson, S; Robert, C; Williams, TG; Liang, F-H; Choi, W; Davis, TA; Babic, S; Boyce, H; et al. (Oxford University Press, 2024)
Early-type galaxies (ETGs) are known to harbour dense spheroids of stars but scarce star formation (SF). Approximately a quarter of these galaxies have rich molecular gas reservoirs yet do not form stars efficiently. We study here the ETG NGC 524, with strong shear suspected to result in a smooth molecular gas disc and low star-formation efficiency (SFE). We present new spatially resolved observations of the 12CO(2-1)-emitting cold molecular gas from the Atacama Large Millimeter/sub-millimeter Array (ALMA) and of the warm ionized-gas emission lines from SITELLE at the Canada–France–Hawaii Telescope. Although constrained by the resolution of the ALMA observations (≈37 pc), we identify only 52 GMCs with radii ranging from 30 to 140 pc, a low mean molecular gas mass surface density ⟨Σgas⟩ ≈ 125 M⊙ pc−2 and a high mean virial parameter ⟨αobs, vir⟩ ≈ 5.3. We measure spatially resolved molecular gas depletion times (τdep ≡ 1/SFE) with a spatial resolution of ≈100 pc within a galactocentric distance of 1.5 kpc. The global depletion time is ≈2.0 Gyr but τdep increases towards the galaxy centre, with a maximum τdep, max ≈ 5.2 Gyr. However, no pure H ii region is identified in NGC 524 using ionized-gas emission-line ratio diagnostics, so the τdep inferred are in fact lower limits. Measuring the GMC properties and dynamical states, we conclude that shear is the dominant mechanism shaping the molecular gas properties and regulating SF in NGC 524. This is supported by analogous analyses of the GMCs in a simulated ETG similar to NGC 524.